SYMPTOMATIC MODERATE CAROTID STENOSIS (50–69%) — RETROSPECTIVE ANALYSIS - Sousa, Pedro Pinto (2019)
Introduction: The European Society for Vascular Surgery (ESVS), following the most validated data published by North American Symptomatic Carotid Endarterectomy Trial (NASCET), European Carotid Surgery Trial (ECST) and Symptomatic Veterans Affairs Co-operative Study Trial (SVACS), determina, regarding symptomatic carotid endarterectomy, designated carotid endarterectomy (CEA) to be considered for patients reporting carotid territory symptoms within the preceding 6 months and diagnosed with moderate (50–69%) carotid stenosis (MCS)(1). Aims: Analyse the admitted patients with MCS, scrutinise the therapeutic orientation and evaluate its adequacy. Materials and methods: The authors retrospectively studied all consecutive patients admitted at one single Institution with symptomatic MCS between 2011–2016. After data collection, patients that were guided to best medical treatment (BMT) were encompassed in Group I, those allocated to carotid endarterectomy (CEA) plus BMT were on Group II and those allocated to carotid stenting (CAS) plus BMT were on Group III. Afterwards we proceeded with a statistical analysis of the results obtained concerning outcomes during follow-up. Results: Group I included 38 patients, 25 males, with a mean age of 74,5 years old. During first year follow-up, was regis- tered one stroke and two transient ischemic attack (TIA) accounting three events (7,9%). Relatedly, 8 patients (21%) died of non-related cause. Group II included 29 patients, 24 males, with a mean age of 72 years old. As peri-operative outcomes was registered two strokes, one causing the death of the patient, accounting two events (6,5%). Finally, in Group III were included 19 patients, 14 males, with a mean age of 76,3 years old. As peri-operative outcomes were registered two strokes, one leading to the death of the patient, accounting two events (10.5%). Discussion/Conclussion: We found a significant statistical difference (p=0,038) favouring BMT plus CEA in place of Stenting plus BMT in accord with already published evidence. Despite higher events registered in the BMT Group, the difference, when compared to CEA plus BMT was not substantial (p=0,67).Despite the reduced pool of patients analysed requiring further studies, according to these results, we believe that once presented with a patient with symptomatic MCS, CEA plus BMT should be offered whenever possible. Still, we consider that there may exist some high risk for CEA patients in whom we should allocate to BMT alone and repetitive re-evaluation considering CEA when neurological stabilization.